Examining the motivation-performance relationship in competitive sport: A cluster-analytic approach - Gillet, N.; Berjot, S.; Vallerand, R. J.; Amoura, S.; Rosnet, E. (International Journal of Sport Psychology, 2012)
In the present research, we adopted a person-centered approach for identifying motivational profiles. Both in junior national fencers (Study 1) and long-distance running athletes (Study 2), cluster analyses showed three motivational profiles: a Low group, a Moderate group, and a High group. In both studies, results also revealed that athletes characterized by the High motivational profile obtained the highest levels of performance. Finally, in Study 2, results revealed that such better performance was achieved at a cost, as athletes in the High group displayed higher levels of emotional and physical exhaustion than those in the Low and Moderate clusters. Theoretical and practical implications of the findings are discussed.